25-OHD response to vitamin D supplementation in children: effect of dose but not GC haplotype. Issue 2 (7th July 2021) - Simpson, Christine A; Zhang, Jane H; Vanderschueren, Dirk; Fu, Lei; Pennestri, Teresita C; Bouillon, Roger; Cole, David E C; Carpenter, Thomas O
Abstract : Objective: GC/DBP effects on response to vitamin D supplementation have not been well-studied. Thus we assessed free and total 25-OHD after vitamin D treatment across the six common GC haplotypes. Design: This double-blind, randomized study compared two vitamin D3 doses in healthy, urban-dwelling 6-month to 10-year-old children at-risk for vitamin D deficiency. Randomization was stratified by GC haplotype. Methods: Children were randomized to receive 2800 or 7000 International Units of vitamin D3 weekly. 25-OHD and 1, 25(OH)2 D were sampled at baseline and after 1–6 months of supplementation. Results and conclusions: One hundred ninety-two of 225 enrolled subjects completed the study. After one month, total 25-OHD increased with both doses and were higher with 7000 IU/week (85.5 ± 22.8 nmol/L) compared to 2800 IU/week (76.8 ± 18.0 nmol/L), despite equivalent baseline levels. No further significant increase occurred at 6 months (89.8 ± 35.5 and 74.3 ± 18.3 nmol/L, respectively). Free 25-OHD similarly changed. 25-OHD differed among GC groups at baseline. Although no significant effects of individual GC haplotypes on incremental changes were evident, a trend toward an effect of combined 'at risk' GC alleles on response was evident ( P  = 0.06). Total 1, 25(OH)2 D showed modest increases, moreso with the larger dose. In urban-dwelling children at-risk for vitamin D deficiency, 1 month of vitamin D3 2800 IU/week increased 25-OHD across all GC haplotype groups, and somewhat enhanced with 7000 IU/week with no further significant increases after 6 months of supplementation. Free 25-OHD measures offer no monitoring advantage over total 25-OHD.